Effect of Passive Ultrasonic Irrigation over Organic Tissue of Simulated Internal Root Resorption - Amjad Abu Hasna; Jaiane Bandoli Monteiro; Ricardo Toledo Abreu; Wanessa Camillo; Amanda Guedes Nogueira Matuda; Luciane Dias de Oliveira; Cesar Rogério Pucci; Cláudio Antonio Talge Carvalho (Hindawi Limited, 2021)
This study aimed to evaluate the efficacy of passive ultrasonic irrigation (PUI) on dissolving the organic tissue inside simulated internal root resorption (IRR) using sodium hypochlorite (NaOCl) or chlorhexidine (CHX). A total of 40 human lower premolars were collected based on dimensional and morphological similarities. The roots were embedded in cylinders (3 cm diameter; 2.5 cm height) of self-cured acrylic resin, and then an IRR was simulated. The specimens were divided into 4 groups (n = 10) according to irrigation protocols: group 1: CHX + PUI; group 2: CHX; group 3: NaOCl + PUI; group 4: NaOCl. The total irrigation time was 150 s at a flow rate of 5 mL/min. A tissue mass of porcine palatine mucosa was used to simulate the organic tissue, it was weighed before and after the irrigation using an analytic balance, and the difference between both readings was calculated and transferred to percentage values. Data were submitted to statistical analysis using two-way ANOVA (factors: irrigant type and with/without PUI) and Tukey's test for multiple comparisons among the experimental groups (α = 0.05). There was a significant difference in both factors (irrigant: p=0.04; PUI: p≤0.001). The groups that used PUI were more effective in dissolving the organic tissue of the IRR simulation than the groups without PUI. PUI is more effective than the syringe and needle irrigation in organic tissue dissolution.